Identification of Hub Genes Associated With the Development of Stomach Adenocarcinoma by Integrated Bioinformatics Analysis - Zhang, Kehui; Wang, Jian; Zhu, YingYing; Liu, Xiaolin; Li, Jiacheng; Shi, Zhe; Cao, Mengxing; Li, Yong (Frontiers in Oncology, 2022)
Objective: A better understanding of the molecular mechanisms of stomach adenocarcinoma which was necessary to predict prognosis and develop novel gene therapy strategies. Methods：In this study, the gene expression profile of GSE118916 was used to explore the differential co-expression genes of STAD and normal tissues. Results：A total of 407 STAD samples were collected, including 375 from stomach adenocarcinoma tissues and 32 from normal tissues, as well as RNAseq count data for 19,600 genes. 42 differentially expressed genes were screened by WGCNA and differentially expressed gene analysis. According to the function annotation analysis of RclusterProfiler package, these genes are analyzed for GO function enrichment, digestion (biological process), tube bottom material membrane (cell component) and oxidoreductase activity (molecular function). KEGG pathway were enriched in gastric acid secretion and chemical carcinogenesis. In addition, Cytoscape's CytoHubba plug-in was used to identify 7 hub genes in a protein-protein interaction (PPI) network consisting of 7 nodes and 11 edges. Compared with normal tissues, CLTC and TP53 genes were up-regulated in stomach adenocarcinoma. TP53 was expressed differently in stage II and stage IV, EWSR1 was expressed differently in stage II and stage III, and ESR1 was expressed differently in stage I, Stage II and stage III. Among the 7 hub genes, KaplanMeier analysis and TCGG showed that the expression levels of HDAC1 and CLTC were significantly correlated with OS in patients with stomach adenocarcinoma. GEPIA2 analysis showed that ESR1 expression was closely correlated with OS and DFS in gastric adenocarcinoma. Then, we collected 18 pairs of gastric mucosal tissues from normal people and cancer tissues from patients with stomach adenocarcinoma. The expression levels of the above 7 hub genes and relative protern expression were detected by PCR and immunohistochemistry. The results showed that the expression in stomach adenocarcinoma tissues waere higher than that in the normal group. Conclusion: In summary, we believe that the identified hub genes were related to the occurrence of stomach adenocarcinoma, especially the expression of ESR1, HDAC1, and CLTC genes, which are related to the prognosis and overall survival of patients, and may become the potential for future diagnosis and treatment.